(untitled) (The Journal of Psychology and Sociology, 2017)
The article examines the problems of employment and unemployment of university graduates on the basis of an expert interview. Researchers explain that changes in the employment situation have been associated not only with the increased level of alumni claims to the workplace, but also the rating of employers’ demands for job applicants. In modern economic conditions, the role of professional and personal qualities is increasing, ensuring competitiveness in the labor market, building a successful professional career. There is an objectively conditioned contradiction between the possibilities of training specialists in the university and the needs for its knowledge and skills in the labor market. The purpose of the study is to identify the most preferable characteristics of university graduates in hiring. Methodology of the study. The research of the opinions of the expert employers was conducted using semi-structured interviews with narrative elements. The study tool included semi-closed questions, with the possibility of including a respondent’s own response. Some of the questions were of an open type, the answers to which were received in the form of free conversation with recording in an audio device. Transcripts of interviews were subjected to qualitative analysis. In the study participated top managers and HR managers of companies. Results of the study. «I’m in the profession,» responsible performance of their functional duties. In the process of work, the respondents encountered a problem that describes the situation as «dealing with those who did not receive higher education but higher education diplomas». Key words: labor market, employers, experts, university graduates, professional qualities, skills and competencies, unemployment.